The Representation of Sea Salt Aerosols and Their Role in Polar Climate Within CMIP6. Issue 6 (14th March 2023) - Lapere, Rémy; Thomas, Jennie L.; Marelle, Louis; Ekman, Annica M. L.; Frey, Markus M.; Lund, Marianne Tronstad; Makkonen, Risto; Ranjithkumar, Ananth; Salter, Matthew E.; Samset, Bjørn Hallvard; Schulz, Michael; Sogacheva, Larisa; et al.
Abstract: Natural aerosols and their interactions with clouds remain an important uncertainty within climate models, especially at the poles. Here, we study the behavior of sea salt aerosols (SSaer) in the Arctic and Antarctic within 12 climate models from CMIP6. We investigate the driving factors that control SSaer abundances and show large differences based on the choice of the source function, and the representation of aerosol processes in the atmosphere. Close to the poles, the CMIP6 models do not match observed seasonal cycles of surface concentrations, likely due to the absence of wintertime SSaer sources such as blowing snow. Further away from the poles, simulated concentrations have the correct seasonality, but have a positive mean bias of up to one order of magnitude. SSaer optical depth is derived from the MODIS data and compared to modeled values, revealing good agreement, except for winter months. Better agreement for aerosol optical depth than surface concentration may indicate a need for improving the vertical distribution, the size distribution and/or hygroscopicity of modeled polar SSaer. Source functions used in CMIP6 emit very different numbers of small SSaer, potentially exacerbating cloud‐aerosol interaction uncertainties in these remote regions. For future climate scenarios SSP126 and SSP585, we show that SSaer concentrations increase at both poles at the end of the 21st century, with more than two times mid‐20th century values in the Arctic. The pre‐industrial climate CMIP6 experiments suggest there is a large uncertainty in the polar radiative budget due to SSaer. Plain Language Summary: Aerosols emitted from the ocean, such as sea salt particles (aerosols), are critical for the climate of polar regions. However, there is still uncertainty in their representation in climate models. The purpose of this work is to evaluate the representation of sea salt aerosols (SSaer) in the Arctic and Antarctic in a recent model inter‐comparison initiative, and to assess the consequences for our understanding of present‐day and future polar climate. We find that the models disagree between them and with observations from ground stations and from space. This suggests that the formulation of sea salt emissions in global models is not adapted for polar regions. With sea ice retreat, SSaer will most likely increase in the future, which makes addressing the current uncertainty an important next step for the scientific community. Key Points: CMIP6 models have a large uncertainty in present day sea salt aerosol abundance at the poles Model performance is degraded closer to the poles suggesting inadequate emission sources within the polar regions Both present and future radiative balance at the poles is uncertain because of sea salt aerosols